Lentil flour as an alternative source of protein - Morales-Herrejón, Yuliza Guadalupe; Márquez-Benavides, Liliana; Herrera-Camacho, José; Cortés-Penagos, Consuelo de Jesús; Yahuaca-Juárez, Berenice (Revista Mexicana de Ciencias Agrícolas, 2025)
Lentils have a high nutritional value and are sustainably grown, due to their protein content, they are an alternative source of protein. Their transformation into flour would facilitate the development of foods, benefiting their nutritional profile and contributing to the diversification of protein sources. The objective was to evaluate the protein quality of green and red lentil flour. The research was conducted at the Faculty of Chemistry-Pharmacobiology, Morelia, Michoacán in 2023. Lentil flours were obtained by grinding the seeds and by traditional cooking (94 °C). A proximate chemical analysis was performed and protein fractions were determined (Osborne method). Protein quality was determined by Score and PDCAAS. Green lentils are high in protein and fiber, red lentils in carbohydrates and ashes. The protein fractions are the majority and were globulins and albumins, and they decreased after cooking. Red lentil flour presented a better digestibility-corrected amino acid profile, with high Score and PDCAAS. In conclusion, lentil flour is an alternative protein source to develop nutritious foods. Future research could optimize its functional and sensory properties through technologies such as extrusion, expanding its use in caloric-protein diets.
Keywords: Lens culinaris M.; legumes; protein fractions; protein quality